2011
DOI: 10.1289/ehp.1002302
|View full text |Cite
|
Sign up to set email alerts
|

The Indian Ocean Dipole and Cholera Incidence in Bangladesh: A Time-Series Analysis

Abstract: BackgroundIt has been reported that the El Niño–Southern Oscillation (ENSO) influences the interannual variation of endemic cholera in Bangladesh. There is increased interest in the influence of the Indian Ocean dipole (IOD), a climate mode of coupled ocean–atmosphere variability, on regional ocean climate in the Bay of Bengal and on Indian monsoon rainfall.ObjectivesWe explored the relationship between the IOD and the number of cholera patients in Bangladesh, controlling for the effects of ENSO.MethodsTime-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 42 publications
(66 reference statements)
5
27
0
Order By: Relevance
“…Temperature is related to food contamination, which may consequently serve as a vehicle for cholera transmission (Rabbani and Greenough, 1999) depending on the physio-chemical properties of the contaminated food. Similarly, rainfall is well documented to have a positive relationship with cholera (Reyburn et al, 2011;Hashizume et al, 2011). The seasonal trend observed in the monthly hospital time series corresponds with the rainy season; this is consistent with what has been found in other regions (e.g.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 88%
“…Temperature is related to food contamination, which may consequently serve as a vehicle for cholera transmission (Rabbani and Greenough, 1999) depending on the physio-chemical properties of the contaminated food. Similarly, rainfall is well documented to have a positive relationship with cholera (Reyburn et al, 2011;Hashizume et al, 2011). The seasonal trend observed in the monthly hospital time series corresponds with the rainy season; this is consistent with what has been found in other regions (e.g.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 88%
“…18 An increase in cholera outbreaks following heavy rainfall is observed in epidemic regions of Africa. 19 Similar observations have been reported in Bangladesh, [20][21][22] Haiti, 9 and East Africa. 23 The role of air temperature has also been highlighted in several recent studies.…”
Section: Resultssupporting
confidence: 81%
“…Previous research in Kolkata and Dhaka have shown that precipitation is associated with an increase in cholera cases most likely caused by the feeding of nutrient-rich runoff into water bodies and flooding of the water supply intended for human consumption with river water harboring V. cholerae. 14,21 DISCUSSION AND SUMMARY Cholera occurrence is characteristically different in epidemic and endemic regions. Epidemic cholera regions are located away from but within 25 miles of a major river system.…”
Section: Cholera In Haitimentioning
confidence: 99%
“…Furthermore, the northern Bay of Bengal is surrounded by densely populated areas, and environmental fluctuations can have important impacts on society. For example, earlier studies demonstrated that SST off Bangladesh was associated with cholera incidence in Dhaka, the capital and largest city in Bangladesh (Lobitz et al 2000;Constatin de Magney et al 2008;Hashizume et al 2011).…”
Section: Introductionmentioning
confidence: 99%